2021
DOI: 10.21037/tlcr-21-572
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment in epidermal growth factor receptor-mutated non-small cell lung cancer before and after epidermal growth factor receptor tyrosine kinase inhibitor treatment: a narrative review

Abstract: Objective: To review and summarize the characteristics of the tumor immune microenvironment (TIME) in EGFR-mutated non-small cell lung cancer (NSCLC) after EGFR-TKI treatment and its role in TKI resistance.Background: Lung cancer is one of the most commonly diagnosed cancer and the leading cause of death from cancer in both men and women around the world. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are considered a first-line treatment for EGFR-mutated NSCLC. However, almost all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 145 publications
1
29
0
Order By: Relevance
“…The enrichment in the extracellular organization pathway, attributed to stromal cells (17), confirms stromal infiltration into the TME for patients resistant to EGFR TKI treatment. Previous studies showed that activation of PD-1 signaling, indicative of immunosuppression, and the PI3K/AKT pathway correlates with EGFR TKI resistance (18), consistent with our observation of increased tumor-stroma interaction in the predicted-not-to benefit group.…”
Section: Tme Image Features Predict Egfr Tki Survival Benefitsupporting
confidence: 92%
“…The enrichment in the extracellular organization pathway, attributed to stromal cells (17), confirms stromal infiltration into the TME for patients resistant to EGFR TKI treatment. Previous studies showed that activation of PD-1 signaling, indicative of immunosuppression, and the PI3K/AKT pathway correlates with EGFR TKI resistance (18), consistent with our observation of increased tumor-stroma interaction in the predicted-not-to benefit group.…”
Section: Tme Image Features Predict Egfr Tki Survival Benefitsupporting
confidence: 92%
“…EMT is emerging as a crucial target for anticancer therapy in combination with the agents eradicating tumor bulk. 44 In sum, this study suggests that melatonin treatment suppressed the growth of NSCLC cells and induced apoptosis. Mechanistic studies indicated that hsa_circ_0017109 was significantly underexpressed in melatonin-treated cells.…”
Section: Discussionmentioning
confidence: 59%
“…Jiang et al 43 summarized that the Hippo pathway is involved in carcinogenesis and progression of NSCLC and SCLC, and high expression levels of YAP and TAZ are independent and novel prognostic factors for lung cancer. EMT is emerging as a crucial target for anticancer therapy in combination with the agents eradicating tumor bulk 44 …”
Section: Discussionmentioning
confidence: 99%
“…Four of the hallmarks of NSCLC tumors are a potential immune-suppressive microenvironment and erratic (and potential inadequate) neovascularization and perfusion caused by changes in the microenvironment [ 39 , 40 , 49 ] resulting in decrease in pH of the tumor microenvironment [ 41 ]. We hypothesized that either of these hallmarks could predict a decreased cellular concentration of the TKIs, even at a high affinity and higher expression of EGFR in the tumor.…”
Section: Methodsmentioning
confidence: 99%